ETIKA JURNALISTIK DALAM PERSPEKTIF HUKUM ISLAM - Zainal Abidin Muhja; Liza Shahnaz (Universitas Borneo Tarakan, 2021)
AbstractThis article highlights the importance of journalistic ethics concerning disseminating information to the public, especially on social media, so that community unity and integrity are maintained and are not easily provoked by false issues. This research is legal research using a normative approach and Islamic literature approach. This research found that a Muslim journalist must put forward several principles: tabayyun, positive thinking, and intention not to spread fake news.Keyword (s): Ethics, Journalistics, Islamic law.